Prevalence and prenatal diagnosis of major congenital anomalies in Dubai: first insights and emerging patterns in a multicenter cohort study - Anne F. Minsart; Hiba Adam; Nadirah Ghenimi; Muna Tahlak; Fadi G. Mirza; Anjum Akbar; Shanthi Sairam (BMC Pregnancy and Childbirth)
Abstract Background Data on the prevalence and prenatal diagnosis of birth defects in Dubai is lacking. There are currently no guidelines specifying the content or standardized technique for performing prenatal ultrasound scans in Dubai. Maternal factors such as higher body mass index, weight gain, advanced maternal age, diabetes, and uterine scarring can affect imaging quality and prenatal anomaly detection, and are becoming more prevalent. Methods The primary objectives were to assess the birth prevalence of major congenital anomalies as defined by EUROCAT and the corresponding prenatal detection rates within a network of tertiary care centers in Dubai between 2019 and 2023. Secondary objectives included comparing prenatal detection based on the location of ultrasound scans - specifically, performed in a network of tertiary care facilities using international ultrasound guidelines versus scans done outside our network, and for scans performed at our facilities, assessing the influence of gestational age, sonologists, and maternal characteristics (body mass index, age, weight gain, diabetes, uterine scarring) through mixed-effect logistic regression. Scan duration and the need for repeat scans were evaluated using Spearman correlation tests. Results The prevalence of major anomalies was 335 (95% confidence interval: 301-372)/10000 live births and stillbirths, and 35.27/10000 for genetic anomalies. Prenatal detection was 70.3% for scans performed in our network, and 46.3% for scans done outside (P<.001). Most women (81.2%) had risk factors for reduced visibility. Scan duration and repeat scans correlated positively with C-sections, maternal age, and body mass index, though weakly. No significant association was found between external factors and prenatal detection (P=.9). Conclusions The prevalence of major anomalies was high. High detection rates were observed in a setting where practitioners come from diverse training backgrounds, and where most patients have risk factors for reduced visibility.